Peningkatan Kinerja Karyawan Melalui Integritas, Teamwork dan Employee Engagement Pada Bagian Lithographing di PT Doulton - Ende Ende; Nurilham Septyadin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Employee performance in PT Doulton especially Lithographing part in particular experienced constraint in the case of decreasing the quantity of work that could result in decreased performance and could result in declining production in Company. This research is direction investigation and knowing the influence between Integrity, Teamwork, Employee Engagement with Employee Performance in the lithographing section at PT Doulton. The total population is 105 employees and the study sample is 83 employees. this method of research is an associative descriptive method Based on research analysis obtained the results values; Calculations in the form of coefficient of determination (R2) have a value of 38,9%. The-t hypothesis test result of an integrity variable earns a value of 4,667, teamwork earns a value 2,573, employee engagement earns a value 4,358, which is greater than 1,990 and the value of sig. Smaller than 0,05. The results of simultaneous research get the following results; Fcount of 16,780 is greater than the ftable of 2,720. the research results can be concluded that the relationship between integrity variables, Teamwork, and Employee Engagement is partial and simultaneous to performance Employees have a positive influence that is even very significant.